2021
DOI: 10.4103/apjon.apjon-2137
|View full text |Cite
|
Sign up to set email alerts
|

Definition and recommended cultural considerations for advance care planning in Japan: A systematic review

Abstract: Although Delphi studies in Western countries have provided a consensus for practices pertaining to advance care planning (ACP), their findings may not be applicable to Asian countries with distinct, family-oriented cultures. This systematic review aimed to synthesize the definitions of and evidence for ACP and analyze recommended practices in Japan. We conducted a systematic review using narrative synthesis in December 2018. Key words were searched from Ichushi-Web by NPO Japan Medical Abstracts Society, Citat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
8
1
1
Order By: Relevance
“…Available evidence has shown that patients’ preferences for communication approach vary across different cultures. For instance, Asian immigrants in Western countries [ 25 , 26 ] and Japanese patients [ 27 ] were likely to prefer implicit communication. In contrast, Western patients preferred information delivered straight to the point and professionally [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence has shown that patients’ preferences for communication approach vary across different cultures. For instance, Asian immigrants in Western countries [ 25 , 26 ] and Japanese patients [ 27 ] were likely to prefer implicit communication. In contrast, Western patients preferred information delivered straight to the point and professionally [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a fact that the need for ACP has been increasing in these areas. To promote ACP, municipalities should develop a collaborative support system through which interdisciplinary HCPs can improve their understanding of each occupation through training [ 24 ]. It is necessary to take actions that encourage the implementation of activities for HCP.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, studies on the decision‐making process for medical treatment and end‐of‐life care had been conducted since 1987, 6 and the incident of the removal of a ventilator for euthanasia at the Imizu Municipal Hospital (Imizu City, Toyama Prefecture, Japan) in 2006 resulted in rapid progress on the decision‐making for medical treatment and end‐of‐life care in recent years. 7 Subsequently, “Guideline for the Decision‐Making Process for Terminal Care” was formulated in 2007. 8 The guideline includes the following points: (1) appropriate information and explanations about end‐of‐life medical care should be provided by doctors and other medical professionals, (2) patients should consult with medical professionals before making any decisions, and (3) decisions regarding medical treatment and end‐of‐life care should be made carefully by the medical and care team, not by doctors on their own.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, studies on the decision‐making process for medical treatment and end‐of‐life care had been conducted since 1987, 6 and the incident of the removal of a ventilator for euthanasia at the Imizu Municipal Hospital (Imizu City, Toyama Prefecture, Japan) in 2006 resulted in rapid progress on the decision‐making for medical treatment and end‐of‐life care in recent years 7 . Subsequently, “Guideline for the Decision‐Making Process for Terminal Care” was formulated in 2007 8…”
Section: Introductionmentioning
confidence: 99%